Volatile Metabolome and Transcriptomic Analysis of Kosakonia cowanii Ch1 During Competitive Interaction with Sclerotium rolfsii Reveals New Biocontrol Insights - Yoali Fernanda Hernández Gómez; Jacqueline González Espinosa; Griselda Catalina Olvera Rivas; Jackeline Lizzeta Arvizu Gómez; José Humberto Valenzuela Soto; Miguel Angel Ramos López; Aldo Amaro Reyes; Eloy Rodríguez de León; Carlos Saldaña; José Luis Hernández Flores; Juan Campos Guillén (Microorganisms, 2025)
The volatile organic compounds (VOCs) produced by K. cowanii Ch1 play a significant role in the inhibition of the mycelial growth of phytopathogen strains. As a continuation of our previous studies, we aim to elucidate the mechanisms of the responses of K. cowanii Ch1 against S. rolfsii during a colonization competence interaction in the presence and absence of a mixture of bacterial VOCs under in vitro conditions. The results of this study showed that, in the absence of bacterial VOCs, K. cowanii Ch1 cannot compete against S. rolfsii, and the RNA-Seq analysis revealed the differential expression of genes related to the oxidative stress response in K. cowanii Ch1 for survival. However, in the presence of bacterial VOCs, an interesting phenotypical response was observed in K. cowanii Ch1, resulting in the mycelial growth inhibition of S. rolfsii. The upregulated genes were related to the siderophore-mediated iron transport system, zinc ion transport system, antibiotic biosynthesis monooxygenase, carbohydrate metabolism, polyketide synthase modules, and related proteins, and katG was probably related to the phenotype resulting in the formation of gas bubbles by K. cowanii. In addition, the VOC profile analyzed at 36 h for bacterial growth revealed a cocktail with an ability to increase the competence of K. cowanii Ch1 against S. rolfsii in vitro and in vivo. This study provides evidence regarding the key role that VOCs play during the colonization competition involving K. cowanii Ch1, the comprehension of which may enable the development of new biocontrol strategies.